NMR chemical shift pattern changed by ammonium sulfate precipitation in cyanobacterial phytochrome Cph1 - Song, Chen; Kopycki, Jakub; Lang, Christina; Hughes, Jon; Matysik, Jörg (Frontiers in Molecular Biosciences, 2015)
Phytochromes are dimeric biliprotein photoreceptors exhibiting characteristic red/far-red photocycles. Full-length cyanobacterial phytochrome Cph1 from Synechocystis 6803 is soluble initially but tends to aggregate in a concentration-dependent manner, hampering attempts to solve the structure using NMR and crystallization methods. Otherwise, the Cph1 sensory module (Cph1Δ2), photochemically indistinguishable from the native protein and used extensively in structural and other studies, can be purified to homogeneity in >10 mg amounts at mM concentrations quite easily. Bulk precipitation of full-length Cph1 by ammonium sulfate (AmS) was expected to allow us to produce samples for solid-state magic-angle spinning (MAS) NMR from dilute solutions before significant aggregation began. It was not clear, however, what effects the process of partial dehydration might have on the molecular structure. Here we test this by running solid-state MAS NMR experiments on AmS-precipitated Cph1Δ2 in its red-absorbing Pr state carrying uniformly 13C/15N-labeled phycocyanobilin (PCB) chromophore. 2D 13C–13C correlation experiments allowed a complete assignment of 13C responses of the chromophore. Upon precipitation, 13C chemical shifts for most of PCB carbons move upfield, in which we found major changes for C4 and C6 atoms associated with the A-ring positioning. Further, the broad spectral lines seen in the AmS 13C spectrum reflect primarily the extensive homogeneous broadening presumably due to an increase in the distribution of conformational states in the protein, in which less free water is available to partake in the hydration shells. Our data suggest that dehydration indeed leads to motional and electronic structural changes of the bilin chromophore and its binding pocket and is not restricted to the protein surface. The extent of the changes induced differs from the freezing process of the solution samples routinely used in previous MAS NMR and crystallographic studies. AmS preci